THE BIOPHYSICAL REGULATION OF TARGET MORPHOLOGY IN THE PLANARIAN FLATWORM - Durant, Fallon. (2018)
Abstract: Target morphology is the shape to which an animal regenerates upon damage. Understanding the mechanisms by which this pattern memory is stored will reveal how the recapitulation of wide-scale shape is properly executed in regenerating systems by individual cells. The molecular genetics involved in re-patterning planaria have been thoroughly investigated, but to date, this research has not fully satisfied the question of how complex shapes are made. We now know that physiological signals in the form of gap junctions and ion flows are highly important and they, in coordination with these gene networks, have the ability to initiate morphogenetic cascades necessary to re-grow intricate, functional anatomies. We first demonstrate that the anterior/posterior pattern in planaria can be re-written via perturbation of endogenous bioelectric networks in Dugesia japonica. This alteration is stochastic, indicating that bioelectric signaling is able to create multistable anatomical targets with the power to override the genetic determinants of polarity. We next explore how early bioelectric signals are involved in the initial establishment of polarity, even before the first known asymmetrical gene expression event takes place. This indicates that biophysical signaling is not only functionally instructive, but serves as the symmetry-breaking incident that leads to the downstream genetic modulation necessary for correct axial polarity. We created a model to describe how bioelectric signals may assemble morphogen gradients using polar transport in such a way to allow for this high level of control. Using a different species, Girardia dorotocephala, we show that morphological regulation via manipulation of these somatic cell networks extends far beyond anterior/posterior polarity and can even orchestrate the creation of sophisticated head shapes. We show these networks are highly plastic and have the ability to adapt to extreme biophysical environments, including chemical exposures and outer space. The molecular mechanisms that store target morphology may be conserved between other biological networks that employ information storage dynamics such as the brain. Thoroughly understanding how these networks store patterning information, guide morphogenesis, and interact with other cell networks (such as the nervous system or microbial networks), will serve as crucial early steps in the way we revolutionize regenerative medicine.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biology.; Advisor: Michael Levin.; Committee: Kelly McLaughlin, Susan Ernst, Barry Trimmer, and James Monaghan.; Keyword: Biology.